The Effect of Organizational Context on Quality Management in Small and Medium Scale Enterprises of Pakistan - Tariq, Abdul Naveed (2002)
Most of the literature available on quality management (QM) and ISO 9000 in Pakistan is in the form of case studies, conceptual papers, descriptions and prescriptions. The main focus of the study was to identify critical factors for effective implementation of Total Quality Management (TQM) and ISO 9000 certification, so that by managing these critical factors of QM, SMEs of Pakistan could flourish in a competitive world market. This research was an empirical attempt to investigate the relationship between organisational quality context (OQC) and level of quality management (LQM), using data from 94 Small and Medium Scale Enterprises (SMEs). Sample constituted 32 sports, 31 leather, and 30 surgical SMEs while one enterprise was involved in both sports and leather goods manufacturing. The Chronbach's coefficient alpha and confirmatory factor analysis (CFA) were used to measure the internal consistency, reliability, and validity of the six main constructs of the measuring instrument. Descriptive statistics and Pearson-coefficient of correlation gave a feel of the data that further helped to examine the current status of the SMEs towards their OQC. The results indicated that the entrepreneurs were not well aware of the basic concepts of QM and ISO 9000 certifications. Similarly, it was found that the financial position of the SMEs was not good, however, the entrepreneurs were supportive to get ISO 9000 certification for their enterprises despite their poor financial position. Furthermore, descriptive statistics indicated that entrepreneur's perceptions towards the government assistance program (GOVT) to overcome financial constraints (GOVTF) and to increase awareness about QM and ISO 9000 certification (GOVTA) among the SMEs of Pakistan were very poor. Data were further analysed using structural equation modelling (SEM), multiple regression analysis and one-way analysis of variance (ANOVA) techniques. Using SEM, four competing models were developed based on the theoretical framework. Comparison of these competing models illustrated that management commitment (COM) was the most important factor affecting LQM in SMEs which was also supported by the findings from the multiple regression analysis, while COM was significantly affected by the financial position of the SMEs (FINAN), and GOVT. Results of one-way ANOVA indicated that the age of the SMEs and the process of ISO 9000 certification were the two significant factors affecting LQM. In other words the older the firm higher the LQM. Similarly, the SMEs at the advance stages of getting ISO 9000 certification were having better LQM as compared to those with no certification or those at initial stages of the process of certification.Overall findings revealed that OQC had a significant impact on LQM in SMEs. Research presented the outcomes in the fonn of an implementation framework, constructed through the use of practical guidelines, the key steps of which have been validated and supported empirically. This empirical study suggested that knowledge of OQC is useful for explaining and predicting quality management practices (QMPs). This study is the first empirical attempt at studying QM in SMEs (leather, sports and surgical) of Pakistan and would be a step further in synthesising the theory of QM and also a good contribution to the existing literature on QM and ISO 9000 certification in SMEs of developing economies.